2014
DOI: 10.1111/bjh.13100
|View full text |Cite
|
Sign up to set email alerts
|

Phase I‐II trial of oral cyclophosphamide, prednisone and lenalidomide for the treatment of patients with relapsed and refractory multiple myeloma

Abstract: , 32 patients were entered in cohorts of three at three dose levels. The median age was 64 years, 59% were male, with a median two prior regimens. Responding patients could stay on treatment until progression. The full-dose CPR regimen produced no dose-limiting toxicity and was delivered for a median of 16 months (3Á5-65 months) with acceptable safety and tolerance. The overall response rate (≥ partial response) was 94% at a median follow up of 28 months. The median progression-free survival was 16Á1 months [9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…12,27,28 In our study, median PFS was 10.4 months and median OS was not reached, supporting the hypothesis that cyclophosphamide increased the clinical efficacy of pomalidomide.…”
Section: Discussionsupporting
confidence: 74%
“…12,27,28 In our study, median PFS was 10.4 months and median OS was not reached, supporting the hypothesis that cyclophosphamide increased the clinical efficacy of pomalidomide.…”
Section: Discussionsupporting
confidence: 74%
“…[9][10][11][12][13][14][15] Interestingly, a combination of lenalidomide and continuous cyclophosphamide resulted in an ORR of 50% in lenalidomide refractory patients, suggesting cyclophosphamide may be able to overcome resistance to lenalidomide in the clinic. 16 In addition, Larocca et al combined continuous pomalidomide with oral cyclophosphamide.…”
Section: Introductionmentioning
confidence: 99%
“…35 Other studies have also demonstrated a beneficial effect of addition of weekly cyclophosphamide to lenalidomide and corticosteroids in patients with relapsed/refractory lenalidomide-naive MM ($ PR: 65% to 94%). [40][41][42] Because of the high response and prolonged PFS reported in these studies, directly starting with the 3-drug regimen of lenalidomide, cyclophosphamide, and corticosteroid may also be considered, as opposed to adding cyclophosphamide at the time of development of lenalidomide-refractory disease. Furthermore, a retrospective analysis showed high efficacy ($ PR: 68%) and good tolerability of lenalidomide, low-dose cyclophosphamide, and prednisone in relapsed/refractory MM patients who were previously exposed to lenalidomide-dexamethasone (39% lenalidomide refractory).…”
Section: Discussionmentioning
confidence: 99%